Keutamaan Al-Qur’an: Kitab Petunjuk Universal di Era Digital - Desrivariza, Putri; Aulia, Dinda; Iskandar, Intan Cahya; Dahrani, Eza Fira; Wismanto, Wismanto (Faidatuna, 2024)
The Al-Qur’an, the holy book revealed to the Prophet Muhammad SAW, has a special position in the lives of Muslims. As the main source of Islamic teachings, the Qur’an provides comprehensive instructions on how humans should live, both in relation to God, fellow humans, and the universe. This research aims to describe and analyze the primacy of the Koran in the digital era and how this holy book is relevant in responding to challenges and problems that arise today. The type of research used is descriptive-analytical research. It is proven that the Koran remains relevant and even more important in the digital era. Even though the Koran was revealed more than 1,400 years ago, its contents include universal values ​​that can be applied in every era. Principles such as justice, truth, integrity, compassion, and balance between worldly and spiritual life remain basic human needs, especially amidst the rapid changes brought about by technology. In a digital context, the Koran is an important guide for humans to adhere to eternal moral values. The Koran remains superior as a source of relevant life guidance in the digital era.